What works and what does not work in local entrepreneurship support policy? - Jacek Rodzinka; Tomasz Skica; Elżbieta Ociepa-Kicińska; Rafał Czyżycki (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The article aims to determine the influence of specific entrepreneurship support instruments in each type of municipality on the increase entrepreneurship level as measured by the number of newly established companies in the area. Research Design & Methods: A survey was conducted among 896 Polish municipalities, asking about four areas of entrepreneurship support: cooperation of the commune with entrepreneurs; finance, tax, and administration support; attracting investors, granting external funds by the commune; and supporting non-governmental organizations. To determine the relationship between the type of commune, the instrument used, and the effectiveness of the tool used, we used a generalized reduced gradient non-linear algorithm. Findings: The study results proved that there is no one universal area or instrument that would guarantee with high probability success in the form of an increase in the level of entrepreneurship in a municipality, regardless of its type. It was shown that in specific types of municipalities, it is possible to identify tools that are more effective than others. Implications & Recommendations: This knowledge can and should provide important guidance to decision-makers at the local level, showing tools that may work better in their type of municipality. Contribution & Value Added: The identification of specific tools that work for a particular type of municipality is an important stimulus in the discussion on strengthening the effectiveness of Polish municipalities' policies.
Keywords: L26; L38; 330; entrepreneurship; local development; local government support; municipal entrepreneurship; support instruments